Developing a Prototype of a Self-Regulated Learning-Based Learning Model for English Language Learning for Junior High School: Introduction, The Objectives, Method, Result and Discussion, Conclusion - Sutiono, Cayandrawati; Novita Triana; Elvina Arapah; Kamal, Sirajuddin (Yayasan Ilomata, 2025)
This study aims to develop a prototype learning model based on self-regulated learning for students who study English at Junior High School, and find effective strategies to support teachers in adopting and adapting self-regulated learning-based learning in their English classes. The era of globalization requires mastery of English language to access global information, communicate among countries, and increase competitiveness. The 2045 Golden Indonesia Vision [5 also emphasizes the importance of developing the quality of human resources, including English language. However, data show that Indonesia English language proficiency is still low according to EF English Proficiency Index. Also, one of the main challenges is the very limited use of English language in daily life. The conditions mentioned above are challenges for the autonomous learning of high school students. Therefore, a teaching and learning model facilitating students with the ability to systematically manage their learning process is really needed to achieve their learning goals. The components of SRL include cognitive strategies, beliefs and motivation, and resource management. The self-regulated learning-based learning model is seen as the right solution to improve students' self-regulated abilities in learning English language. This learning model follows a three-phase cycle model which includes the Forethought phase, the Performance phase, and the Reflection phase. Developing the prototype of a Self-Regulated Learning-Based Learning Model for Junior High School English participants follows the ADDIE Model. This development model has 5 stages: Analysis, Design, Development, Implementation and Evaluation. However, there are only three stages of the ADDIE Model implemented in the research, namely Analysis, Design, and Development. Through this study, the prototype of a SRL-based Learning Model is developed. The implications of this prototype are (1) teachers becoming more aware to facilitate students’ learning English with learning strategies, and (2) students are rather more goal and strategy-oriented since they implement the SRL in order to get better achievement.